ARABIC-ISLAMIC STUDIES AT UNIVERSITY LEVEL: ITS IMPORTANCE AND ROLE IN PROMOTING ISLAMIC ETHICS IN SOCIETY - Nargis Mushtaq; Prof.Dr. Abdul Qadir Haroon (دی اسکالر)
The main focus of the article is to highlight the importance of teaching Islamic studies at the university level concerning its role in the promotion of Islamic ethics and morals in society. The article also emphasizes the role of Islamic studies teacher, educational curricula, and teaching methodologies in the moral and spiritual upbringing of the students. And how the subject can play a vital role in the formation of an ideal Islamic society characterized by high moral values. The research has concluded that the development of Islamic studies curricula according to contemporary global challenges, the training of teachers, and the use of modern means in the teaching and learning of Islamic studies is a need of time.